Tumour volume and occurance of pulmonary metastasis in liposarcoma of the extremities - Zainudin, Tunku Naziha Tunku (2017)
Liposarcoma is one of the commonest subtypes of soft tissue sarcoma constituting 9.8-18 % of cases [1]. The World Health Organization ( WHO) classification of tumors of soft tissue and bone 2009 clasiffied liposarcoma into 4 subtypes which were well differentiated, myxoid, pleomorphic and dedifferentiated subtypes. Soft tissue sarcomas metastasize primarily via hematogenous spread in which they usually settled in pulmonary as the main site. Liposarcoma metastasized according to the grade of lesion where high grade liposarcoma had the highest metastasis rate which was 50 % (3). Metastatic disease is the major cause of death in patients with soft tissue malignancies. Hence early detection of metastatic disease has important implications for prognosis and treatment. Tumor size was a readily available risk factor but it has been neglected in large analyses of prognostic factors largely because of its incompleteness and inaccuracy. Tumor volume measurement recently was found to be as accurate and reproducible to be used as prognostic indicator. Therefore we decided to measure the tumor volume via 3- dimensional views from CT or MRI and used OsiriX program to interprete the tumor volume. Then we established the association of tumor volume with overall survival in liposarcoma. Other than that, we also associate other prognostic factors such as demography, histopathological diagnosis, surgical margins and the disease outcome for instance pulmonary metastasis, local recurrence and death with the surgically treated liposarcoma and its overall survival.This study involved a total of 38 patients which fulfilled the inclusion and exclusion criteria, were selected from 1st January 2001 till 31st December 2014. We found out there were differences with median tumor volume according to liposarcoma subtypes, with higher grade tumor presented with smaller tumor volume. Larger than median tumor volume was associated in patients with increased depth of tumor, absence of adjuvant chemotherapy and presence of pulmonary metastasis. Overall survival in our study was significantly influenced by presence of pulmonary metastasis. Tumor volume and other prognostic factors were not associated with worsening overall survival. Therefore we made the conclusion there was significant association between tumor volume with increased depth of tumor, absence of adjuvant chemotherapy and presence of pulmonary metastasis. Overall survival in this study was associated with presence of pulmonary metastasis and was not influenced by the tumor volume.